2021
DOI: 10.1021/acs.joc.1c00472
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoquinolones by Sequential Suzuki Coupling of 2-Halobenzonitriles with Vinyl Boronate Followed by Cyclization

Abstract: A novel, facile, and expeditious two-step synthesis of 3,4-unsubstituted isoquinolin-1­(2H)-ones from a Suzuki cross-coupling between 2-halobenzonitriles and commercially available vinyl boronates followed by platinum-catalyzed nitrile hydrolysis and cyclization is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The three putative EGFR‐sparing core scaffolds, SJF‐4601, DHC‐7657 and DC‐6142, were synthesized as shown in Scheme 1a–c. Concise synthesis of the isoquinoline scaffold of DHC‐7657 was enabled by the methodology recently reported by our lab [23] …”
Section: Resultsmentioning
confidence: 99%
“…The three putative EGFR‐sparing core scaffolds, SJF‐4601, DHC‐7657 and DC‐6142, were synthesized as shown in Scheme 1a–c. Concise synthesis of the isoquinoline scaffold of DHC‐7657 was enabled by the methodology recently reported by our lab [23] …”
Section: Resultsmentioning
confidence: 99%
“…Concise synthesis of the isoquinoline scaffold of DHC-7657 was enabled by the methodology recently reported by our lab. [23] We first sought to validate that our new scaffolds retained their ability to bind brachyury using LCMS (Figure 2d). Compounds were incubated with brachyury DBD for 5 hours.…”
Section: Design and Synthesis Of Egfr-sparing Scaffolds That Retain B...mentioning
confidence: 99%
“…Figueroa et al reported a simple and efficient two-step synthesis of isoquinolinone 13 (Scheme 1). 42 Suzuki coupling between vinyl boronate ester 10 and 2-halobenzonitriles 9 leads to a vinyl ether adduct 11 that generates an amide–aldehyde intermediate 12 on hydrolysis. Compound 12 then switches to cascade cyclization followed by dehydration affording isoquinolone 13 .…”
Section: Transition Metal-mediated Cascade Reactionsmentioning
confidence: 99%